2018
DOI: 10.1101/397943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Visual Capture Towards Subjective Embodiment Within the Full Body Illusion

Abstract: Typically, multisensory illusion paradigms emphasise the importance of synchronous visuotactile integration to induce subjective embodiment towards another body. However, the extent to which embodiment is due to the 'visual capture' of congruent visuoproprioceptive information alone remains unclear. Thus, across two experiments (total N = 80), we investigated how mere visual observation of a mannequin body, viewed from a first-person perspective, influenced subjective embodiment independently from concomitant … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 83 publications
(126 reference statements)
6
17
0
Order By: Relevance
“…However, this reduction in pleasantness for CT-optimal touch to the abdomen was not supported by a parallel increase in the intensity sensation experienced by participants at the same body site, given that overall, touch to the back but not to the abdomen was felt as the least intense. Contrary to our prediction, but in line with recent studies investigating whether perceived pleasantness of touch was modulated by subthreshold EDs psychopathology in two samples of healthy females [ 77 , 78 ], we did not find evidence to support the idea of an association between preference for CT-optimal (3 cm/s) touch when applied to the abdomen and individual differences in any of the affective body image components. Interestingly however, exploratory analyses showed that perceived tactile preference for CT-optimal (3 cm/s) touch delivered to the back, was predicted by individual differences in body awareness (BPQ).…”
Section: Discussionsupporting
confidence: 59%
“…However, this reduction in pleasantness for CT-optimal touch to the abdomen was not supported by a parallel increase in the intensity sensation experienced by participants at the same body site, given that overall, touch to the back but not to the abdomen was felt as the least intense. Contrary to our prediction, but in line with recent studies investigating whether perceived pleasantness of touch was modulated by subthreshold EDs psychopathology in two samples of healthy females [ 77 , 78 ], we did not find evidence to support the idea of an association between preference for CT-optimal (3 cm/s) touch when applied to the abdomen and individual differences in any of the affective body image components. Interestingly however, exploratory analyses showed that perceived tactile preference for CT-optimal (3 cm/s) touch delivered to the back, was predicted by individual differences in body awareness (BPQ).…”
Section: Discussionsupporting
confidence: 59%
“…While in certain experimental conditions it has been suggested that 1PP alone (Carey, Crucianelli, Preston, & Fotopoulou, 2019;Maselli & Slater, 2013;Slater, Spanlang, Sanchez-Vives, & Blanke, 2010), or multi-sensory correlation alone (Lenggenhager, Tadi, Metzinger, & Blanke, 2007), might be sufficient to elicit the embodiment illusion, the combination of the two seems crucial to induce sense of embodiment, especially as the resemblance of the avatar body becomes increasingly different to the human body in appearance (Maselli & Slater, 2013).…”
Section: Minimum Conditions Necessary For Experiencing Sense Of Embodiment In Mediated Embodimentmentioning
confidence: 99%
“…While in certain experimental conditions it has been suggested that 1PP alone (Carey, Crucianelli, Preston, & Fotopoulou, 2019;Maselli & Slater, 2013;Slater, Spanlang, Sanchez-Vives, & Blanke, 2010), or multi-sensory correlation alone (Lenggenhager, Tadi, Metzinger, & Blanke, 2007), might be sufficient to elicit the embodiment illusion, the combination of the two seems crucial to induce sense of embodiment, especially as the resemblance of the avatar body becomes increasingly different to the human body in appearance (Maselli & Slater, 2013).…”
Section: Minimum Conditions Necessary For Experiencing Sense Of Embodiment In Mediated Embodimentmentioning
confidence: 99%